Infrastructure Development, Capacity Utilization and Manufacturing Value Added in Nigeria - Edeme, Richardson Kojo; Nchege, Johnson; Dorathy, Idiota (The Economics and Finance Letters, 2020)
One of the greatest challenges being grappled with by most developing countries is to boost manufacturing sector performance. In achieving this however, emphasis has been laid on the role of infrastructural development coupled with utilization of capacity in the manufacturing sector. Previous studies have focused on the effect of infrastructure on manufacturing productivity. This study differs from the rest by examining the impact of infrastructure development and capacity utilization on manufacturing value added, using Nigeria data from 1980-2019. Our framework of analysis employed electricity, average capacity utilization, government capital expenditure and manufacturing value added annual percentage growth as variables of analytical relevance. Finding indicates that electricity had negative and insignificant effect on manufacturing value added while manufacturing capacity utilization and capital expenditure had positive and significant effect on manufacturing value added. The result reiterates that capital expenditure on social and economic infrastructure has the capacity to improve manufacturing value added.